Semantic number in relation to English language learner awareness - Aneta Naumoska (Educational Role of Language Journal, 2020)
This paper focuses on semantic number in English and its effect on students’ understanding of countability and how they see the world through English. Semantic nominal plurality of reference is not always equivalent to a marked plural noun or S-V plural agreement. The paper aims to explain and illustrate whether morphosyntactic markedness of number coincides with semantic specificity/informativity, and if EFL learners’ worldview shifts depending on their awareness of semantic number. The linguistic issue of number is paired with education, i.e. learners’ development in a foreign language framework. The research was targeted towards English majors (Faculty of Philology, Skopje, N. Macedonia), whose knowledge of number agreement (competence) in English was explored via a questionnaire covering various instances of number inconsistencies. It is noteworthy that most students afterwards stated a rising level of confidence in communicating in English due to a higher level of language accuracy and semantic awareness.